Molecular imaging of brain localization of liposomes in mice using MALDI mass spectrometry - Fülöp, Annabelle; Hopf, Carsten (Scientific reports, 2016)
Phospholipids have excellent biocompatibility and are therefore often used as main components of liposomal drug carriers. In traditional bioanalytics, the in-vivo distribution of liposomal drug carriers is assessed using radiolabeled liposomal constituents. This study presents matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI MSI) as an alternative, label-free method for ex-vivo molecular imaging of liposomal drug carriers in mouse tissue. To this end, indocyanine green as cargo and two liposomal markers, 1,2-dipalmitoyl-sn-glycero-3-phosphoglycerol (DPPG) and 1,2-distearoyl-sn-glycero-3-phosphoethanolamine conjugated with monodisperse polyethylene glycol (PEG36-DSPE) were incorporated into liposomal carriers and administered to mice. We used MALDI MSI of the two lipid markers in both positive and negative ion mode for visualization of liposome integrity and distribution in mouse organs. Additional MSI of hemoglobin in the same tissue slice and pixel-by-pixel computational analysis of co-occurrence of lipid markers and hemoglobin served as indicator of liposome localization either in parenchyma or in blood vessels. Our proof-of-concept study suggests that liposomal components and indocyanine green distributed into all investigated organs.
Gesehen am 06.08.2019